Role of Diagnostic Rigid Nasal Endoscopy in the evaluation of bleeding points and management of Epistaxis (Birat Journal of Health Sciences, 2023)
Introduction: Epistaxis is one of the most common ENT emergencies. Causes of epistaxis can be idiopathic, local, or associated with systematic conditions. Anterior rhinoscopy gives a limited view of the nasal cavity. Difficulty in the localization of bleeding points on anterior rhinoscopy is commonly encountered. We often face difficulty in the localization of bleeding points, especially the hidden areas. Nasal endoscopy helps to identify the hidden bleeding points and specifically control the bleeding.Objective: The main aim of our study was to visualize bleeding points and demonstrate the efficacy of nasal endoscopy in identifying the bleeding site and controlling epistaxis without nasal packing.Methodology This is a cross-sectional study done on patients who presented to the ENT Outpatient Department with complaints of nasal bleeding. They were evaluated by rigid nasal endoscopy for localization of bleeding points as well as control of epistaxis.Results: Highest number of cases were seen in the 26-35 years of age group. 69.7% (n=53) patients presented with anterior epistaxis and 28.9% (n=22) had posterior epistaxis. Most of the patients i.e.,57.9 %(n=44) had no obvious abnormality associated with epistaxis, followed by Deviated Nasal Septum with septal spur i.e.,34.2%(n=26). On localizing the bleeding points, 77.6% (n=59) of bleeding points were seen on the septum. 57.9% (n=44) of patients developed epistaxis on the right side. 58% (n=52) of patients were managed with endoscope-assisted chemical cauterization followed by endoscope-associated electro-cauterization using bipolar cautery.Conclusion: Rigid nasal endoscopy not only helps in localizing bleeding points but also in managing the cases and is gradually replacing conventional techniques like anterior and posterior nasal packing.